EVALUATION OF CONVENTIONAL AND SHARIA STOCK PERFORMANCE BASED ON SHARPE, TREYNOR, AND JENSEN INDECES - Usama Abdullah Fikri; Kurniawati Meylianingrum (I-Finance Journal, 2024)
The purpose of the research is to analyse the performance of conventional and sharia stocks in the Indonesian capital market for the 2019-2023 period. the LQ45 and JII indices are used as proxies to represent each of the conventional and sharia stocks. The method used in this research is descriptive method, where the evaluation of the performance of conventional and sharia stocks is measured based on the sharpe, treynor, and jensen indices. The population in this research are all stocks included in the LQ 45 and JII indices in the 2019-2023 period. The samples in this study were 19 conventional stocks from the LQ 45 indices and 13 Islamic stocks from the JII indices. The sampling method used is non-probability sampling with a purposive sampling approach. the results of this study show several stocks that have performed well during the 2019-2023 period, in conventional stocks, namely: ADRO, ANTM, BBRI, ICBP, INCO, ITMG. While in sharia stocks, namely ADRO, ANTM, ICBP, INCO. These stocks can be considered by investors to be included in the investment portfolio. The conclusion of this study is that the performance of conventional and sharia stocks based on the Sharpe, Treynor, and Jensen, value of stocks is dominated by negative values, which means that the condition of stock analysis is quite bad compared to the portfolio, portfolio beta, and the market or benchmark used.